If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 35 + 15x = 17x Solving 35 + 15x = 17x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17x' to each side of the equation. 35 + 15x + -17x = 17x + -17x Combine like terms: 15x + -17x = -2x 35 + -2x = 17x + -17x Combine like terms: 17x + -17x = 0 35 + -2x = 0 Add '-35' to each side of the equation. 35 + -35 + -2x = 0 + -35 Combine like terms: 35 + -35 = 0 0 + -2x = 0 + -35 -2x = 0 + -35 Combine like terms: 0 + -35 = -35 -2x = -35 Divide each side by '-2'. x = 17.5 Simplifying x = 17.5
| fx-gx=hforx | | 3(x+4)+x=(2x-7) | | -2x+2+3x=6 | | 7p-(p+4)=-2(2p-1)+10 | | 3-x+4x=6 | | 5+7x-x=71 | | X+1.5x= | | 7x-7y=5solvey | | 4nsquared+4n-168=0 | | k=gd | | 21x+1=4 | | 6m+6(6m-3)=108 | | 10-5t=6t-23 | | f(x)=ln(e^2x) | | y+3=.5(x-4) | | 16y^8= | | 3x+84=75 | | 72x+9y=18 | | 13x=2(5x+3) | | 9(x+7)+10=11x-2(x-3) | | 24-2x=14x-21 | | 3x^3+8x=420 | | 5b^4=134 | | 5+3(3x-5)=5-4(2x+1) | | 3x^2+8x=420 | | 2cosx=1-sinx | | f(x)=x^3-3x^2-9x+12 | | 0.8(x+300)=0.84x-56 | | 14-x^4= | | 2cos^2x+2cosx-1=0 | | 0.87y+2=y-0.6 | | 23.4=7.8*n |